Participation Of Community in Managing Tourism Object Guruh Gemurai Waterfall in Desa Kasang Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - Marlina, Susi; Yoza, Defri; Sulaeman, Rudianda (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Since 2008, tourism department Kuantan Singingi district has let to the local community to manage the Guruh Gemurai waterfall in Desa Kasang Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi. As long as, the local community in managing of the Guruh Gemurai waterfall is not run well. Because of that, the purpose of this research is to find out participation level among people in the community in manage Guruh Gemurai waterfall and to find out the relationship between the condition of economic, social, and culture of the people and participation level. The method of this reseach is Random Sampling. To know the level of participation is used Likert Scale and to know the correlation between participation with social economic and culture is used Chi Square analysis. The result of this study showed the level of community participation in handling Guruh Gemurai waterfall is middle level it is 67,5 %. This case couse, local community just handling in planning and running out. there was a conflict between the local community with tourism department, the characteristic of local community is farmer. Economic, social, and culture factor which have effect to participation level are action in group work tourism, side job and side income in the waterfall area. Social economic factor which don't have effect are education level, duration of recidence around location, number of family member, distance between home and tourism area, knowledge about history of the waterfall, participation in county management, potency of art and culture, main job and main income. Keyword: community's participation, manajement, Guruh Gemurai waterfall.